The State liability in the current rule of law - Delpiazzo Rodríguez, Carlos Enrique (2020)
The creation of legal entities or institutions —instrumental entities of the government administration— to implement a change in the system of the activities assigned to the government administration, is aimed at eluding the administrative law thereby, making the state’s responsibility unviable. However, this distorts the very reason for the existence of the state’s public entities, since it makes no sense to exempt the State from responsibility when the activity that causes the damage has been placed by it, in the hands of a third person who exercises it. Facing this, and considering that a society that fails to recognize that the government administration must meet the general objectives subject to the full extent of the law, «or that recognizing it, adds observations or exceptions thereto, does not truly live under a system of rule of law» (Duguit), the «communicability» of the responsibility has been proposed so that the citizen damaged by a public entity is not deprived of a fair redress